A rational computational study of surface defect-mediated stabilization of low-dimensional Pt nanostructures on TiN(100)1. Issue 15 (21st April 2015) - Tak, Young Joo; Jang, Woosun; Richter, Norina A.; Soon, Aloysius
<x xml:space="preserve">Abstract</x> A rational computational platform to design surface defect-mediated low-dimensional Pt/TiN nanocatalysts for next generation high-performance fuel cell technology via strong electronic metal–support interaction.